Motor learning in children and adolescents institutionalized in shelters - Souza Santos, Caroline Moreira (2017)
Introduction: Children and adolescents living in shelters may present with impaired motor development, cognitive function, as well as speech and understanding; psychological alterations; and hyperactivity. All of these factors may be detrimental to motor learning. Objective: To investigate motor learning in children and adolescents living in shelters, and to compare it with that of individuals living in a family context. Methods: We assessed 36 individuals who were divided into groups: an experimental group, composed of institutionalized children and adolescents (EG, n=18), and a control group (CG, n = 18) that was matched by age and sex. Motor learning was assessed using a maze test in three stages: acquisition, retention and transfer. The data were analyzed using the Shapiro Wilk, Wilcoxon, Mann Whitney, Kruskal Wallis tests and Dunn’s post-test (p < 5%). Results: The EG had a longer task performance time than the CG. There was a significant reduction in task performance time between the first (EG = 11.05 [8.50-14.85]s; CG:7.65 [5.95-10.23]s) and the last task performance block (EG:8.02 [6.86-10.23]s; GC: 5.50 [4.50-6.82]s) in both groups. When comparing the variables of the last acquisition (GE:8.02[6.86-10.23]s; GC: 5.50[4.50-6.82]s), retention (GE:8.20[7.09-9.89] s;GC:5.35[4.50-6.22]s) and transfer blocks (GE:8.30[6.28-11.43]s; GC:5.30[4.90-6.82]s) in each group, wefound no changes in task performance time between test batteries. Conclusion: Individuals living in shelters showed a motor learning deficit, as evidenced by longer task performance time when compared to their controls. Nevertheless, both groups performed the task in a similar manner.